Spontaneous Globe Subluxation in a Neonate: A Case Report with Literature Review - Rani Roy, Soma; Hoque, Md. Asrarul (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
Globe subluxation is a medical emergency and a frightening condition. The spontaneous subluxation is the rarest of the subluxations, with fewer than 40 cases reported to date. This condition is extremely rare in children, with the most recent reported age being 8 months. However, Crouzon syndrome in infants is also less reported. Here we report a case of neonatal Crouzon syndrome with spontaneous globe subluxation and its surgical management.